THE INFLUENCE OF VISUAL AND AUDIOVISUAL INTERACTION OF INSTAGRAM CONTENT ON VISITORS' INTEREST IN KUPIE THAMRIN CULINARY CAFE - Ayunda Safitri; Fatia Amanda; Willy Cahyadi; Cici Puspaningrum (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the effect of visual and audiovisual interaction of Instagram content on visitor interest in Kuliner Kupie Thamrin Cafe. Using a quantitative approach, data was collected through questionnaires from 96 respondents who had interacted with the cafe's Instagram content. Outer Model Analysis was carried out to analyze the validity and reliability of the instrument and Inner Model Analysis was carried out to analyze the structural model and then hypothesis testing and simultaneous tests were carried out. The results showed that audiovisual interaction significantly influenced visitor interest but there was no significant influence between visual interaction and visitor interest. However, simultaneously visual and audiovisual variables have a significant effect on visitor interest with a calculated F value of 59.042 which is greater than Ftable (3.09) at α = 0.05.